2022
DOI: 10.1177/19476035221093065
|View full text |Cite
|
Sign up to set email alerts
|

The Current Status of Clinical Trials on Biologics for Cartilage Repair and Osteoarthritis Treatment: An Analysis of ClinicalTrials.gov Data

Abstract: Objective Biologics are increasingly used for cartilage repair and osteoarthritis (OA) treatment. This study aimed to provide an overview of the clinical trials conducted on this subject. Design Two-word combinations of two sets of key words “cartilage”; “joint”; “osteoarthritis” and “biologics”; “stem cells”; “cell implantation” were used to search the database of ClinicalTrials.gov and supplemented with searches of PubMed and EMbase. The registered trials were analyzed for clinical conditions, completion sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Our data also displayed that the rate of registered trials not achieving publication was alarmingly high (73%), even when compared with publication rates of clinical trials related to orthopedic trauma (43%), 51 biologics for cartilage repair and osteoarthritis (44%), 52 and adult spine surgery (21%). 50 Nonetheless, it is noteworthy that 19.2% of the trials included in the analysis were flagged as completed but lacked any reported results, potentially indicating a concern for publication bias.…”
Section: Discussionmentioning
confidence: 79%
“…Our data also displayed that the rate of registered trials not achieving publication was alarmingly high (73%), even when compared with publication rates of clinical trials related to orthopedic trauma (43%), 51 biologics for cartilage repair and osteoarthritis (44%), 52 and adult spine surgery (21%). 50 Nonetheless, it is noteworthy that 19.2% of the trials included in the analysis were flagged as completed but lacked any reported results, potentially indicating a concern for publication bias.…”
Section: Discussionmentioning
confidence: 79%
“…Joinpoint regression fits a piecewise linear regression model, which is a special case of linear spline [ 13 ]. Early phase 1, phase 1, and phase 2 were combined as early phase, and phases 3 and 4 were combined as advanced phase [ 14 ]. The median age of each trial was compared with the median age of the relevant disease site according to the NCI Surveillance, Epidemiology, and End Results (SEER) database [ 9 , 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, mesenchymal stromal cells (MSCs) have emerged as a promising treatment for OA 11 14 . More than two hundred related clinical trials have been registered at the clinicaltrials.gov 15 . However, the outcomes have been heterogenous and the effects do not last long 16 .…”
Section: Introductionmentioning
confidence: 99%